Optimizing the fitting-surface preparation of zirconia restorations for bonding to dentin. Issue 3 (March 2021) - Franz, Alexander; Winkler, Olivia; Lettner, Stefan; Öppinger, Simon; Hauser, Anna; Haidar, Marwan; Moritz, Andreas; Watts, David C.; Schedle, Andreas
Abstract: Objectives: The aim of this study was to identify the relative strengths and weaknesses of different interfaces within the multilayer structure of a zirconia crown restoration when applying different surface pretreatments. These include the influence on shear strengths of different air abrasion protocols, glaze-on techniques, zirconia primers and self-adhesive cements for either the complex structure: zirconia / self adhesive resin composite cement (RCC) / bovine dentin substrate (part 1) or the RCC / zirconia substrate (part 2). Methods: In Part 1, zirconia discs, pretreated by either glaze-on techniques or air abrasion using Rocatec™ Soft, were bonded to bovine dentin substrates with different self-adhesive RCCs. In Part 2, steel-cylinders were bonded to zirconia cuboid substrates, pretreated by either different protocols for air-abrasion or a glaze-on-technique, with different self-adhesive RCCs. Shear bond strengths (SBS) were measured for all interfacial combinations. Results: In part 1, application of air abrasion using Rocatec™ Soft significantly increased the SBS of zirconia to dentin compared to control specimens without pretreatment, while glaze-on techniques did not increase the SBS. Pretreatment of zirconia surfaces with two primers (either Clearfil Ceramic Primer, or Monobond S) showed significantly higher SBS than the controls. Cementations with RelyX Unicem 2 Automix showed significantly higher SBS than with MaxCem Elite. In Part 2, all air abrasion protocols increased the SBS, but there was no significant difference between these protocols. Again the glaze-on technique did not increase SBS. A significant difference between the two RCCs was again observed. When zirconia substrates were air abraded, regardless of which protocol was applied, the highest SBS were obtained by Calibra with P&B active followed by Panavia with or without Clearfil Ceramic Primer Plus. Calibra applied without P&B active exhibited the lowest SBS. Significance: Pretreatment of zirconia substrates using air abrasion and/or ceramic primers increased the SBS of the zirconia cement interface. For all tested glaze-on treatments, in our experimental setting no effect was observed.